Multidimensional poverty dynamics and health among middle-aged and elderly people: a longitudinal study in China - Shiju Dong; Zexuan Yu; Siqian Zhang; Jiajia Li (Humanities & Social Sciences Communications)
Abstract Previous research has established a link between poverty and adverse health outcomes. In particular, poor health status in the middle-aged and elderly is often irreversible and can make it extremely difficult to escape poverty. Identifying poverty from multiple dimensions and assessing its relationship to health is crucial for active ageing. In this study, we sought to investigate the link between multidimensional poverty, income poverty, and health status using data from the China Health and Retirement Longitudinal Study (CHARLS). Employing panel fixed-effect logistic regression and instrumental variables estimation, we analyzed the impact of multidimensional poverty and income poverty on health status including subjective health, mental health, and physical health. The multidimensional poverty of middle-aged and older adults was classified into three groups: poverty group (n = 3272, 18.04%), precarity group (n = 8234, 36.07%), and prosperity group (n = 11,319, 49.59%). The results of regression analysis indicate that multidimensional poverty is significantly positively correlated with poor self-rated health, poor physical health and mental health, while income poverty is significantly negatively correlated with poor self-rated health, poor physical health and mental health. Moreover, we found that the impact of multidimensional poverty on health is attributed to the reduced healthcare utilization, and compromised health behaviors. This underscores the importance of considering not only income poverty but also multidimensional poverty when examining its association with health status. For promoting healthy aging, it is imperative to comprehensively assess, alert, and address the issue of middle-aged and elderly poverty from a multidimensional perspective.